Accidental Durotomy in Minimally Invasive Transforaminal Lumbar Interbody Fusion: Frequency, Risk Factors, and Management - Jan-Helge Klingler; Florian Volz; Marie T. Krüger; Evangelos Kogias; Roland Rölz; Christoph Scholz; Ronen Sircar; Ulrich Hubbe (The Scientific World Journal)
Purpose. To assess the frequency, risk factors, and management of accidental durotomy in minimally invasive transforaminal lumbar interbody fusion (MIS TLIF). Methods. This single-center study retrospectively investigates 372 patients who underwent MIS TLIF and were mobilized within 24 hours after surgery. The frequency of accidental durotomies, intraoperative closure technique, body mass index, and history of previous surgery was recorded. Results. We identified 32 accidental durotomies in 514 MIS TLIF levels (6.2%). Analysis showed a statistically significant relation of accidental durotomies to overweight patients (body mass index ≥25 kg/m2; P=0.0493). Patient age older than 65 years tended to be a positive predictor for accidental durotomies (P=0.0657). Mobilizing patients on the first postoperative day, we observed no durotomy-associated complications. Conclusions. The frequency of accidental durotomies in MIS TLIF is low, with overweight being a risk factor for accidental durotomies. The minimally invasive approach seems to minimize durotomy-associated complications (CSF leakage, pseudomeningocele) because of the limited dead space in the soft tissue. Patients with accidental durotomy can usually be mobilized within 24 hours after MIS TLIF without increased risk. The minimally invasive TLIF technique might thus be beneficial in the prevention of postoperative immobilization-associated complications such as venous thromboembolism. This trial is registered with DRKS00006135.